Center-Regional Relations in National Motivated Paradiplomacy: A Scottish Case Study - Putri, Anggi Koenjaini; Cakra Diaz Pratama; Ario Bimo Utomo (Universitas Muhammadiyah Yogyakarta, 2025)
This study investigated the complex dynamics of center-regional relations in nationally motivated paradiplomacy, using Scotland as a case study. As a devolved nation within the United Kingdom (UK), Scotland has actively pursued international engagement not merely as a pragmatic exercise in policy diffusion or economic cooperation, but as a strategic vehicle for constructing a distinct national identity. This research identified the nationalist dimension as a primary motive behind Scottish paradiplomacy, particularly under the leadership of the Scottish National Party. Employing a qualitative interpretive approach and a case study method, the study drew upon primary sources (official Scottish government documents, speeches, and international frameworks) and secondary literature spanning 2014 to 2022. Using the analytical lens of paradiplomatic theory and the center-regional relationship typology developed by Panayotis Soldatos, the study concluded that Scotland’s paradiplomacy fits the parallel disharmony pattern. While Scotland and the UK operate simultaneously in international affairs, their motivations, narratives, and policy orientations frequently diverge. Scotland’s emphasis on global citizenship, climate justice, and European engagement stands in stark contrast to London’s centralist and post-Brexit trajectory. This dissonance illustrates how subnational paradiplomacy can serve not only as a policy tool but also as a political instrument for autonomy-seeking entities, challenging conventional notions of sovereignty from below. This study contributes to the broader discourse on paradiplomacy by demonstrating how subnational governments with strong nationalist narratives can develop differentiated external roles within a unitary state structure.